Nano delivery of simvastatin targets liver sinusoidal endothelial cells to remodel tumor microenvironment for hepatocellular carcinoma - Zhuo Yu; Jianfeng Guo; Yun Liu; Menglin Wang; Zhengsheng Liu; Yueqiu Gao; Leaf Huang (Journal of Nanobiotechnology, 2022)
Abstract Background Hepatocellular carcinoma (HCC) developed in fibrotic liver does not respond well to immunotherapy, mainly due to the stromal microenvironment and the fibrosis-related immunosuppressive factors. The characteristic of liver sinusoidal endothelial cells (LSECs) in contributing to fibrosis and orchestrating immune response is responsible for the refractory to targeted therapy or immunotherapy of HCC. We aim to seek a new strategy for HCC treatment based on an old drug simvastatin which shows protecting effect on LSEC. Method The features of LSECs in mouse fibrotic HCC model and human HCC patients were identified by immunofluorescence and scanning electron microscopy. The effect of simvastatin on LSECs and hepatic stellate cells (HSCs) was examined by immunoblotting, quantitative RT-PCR and RNA-seq. LSEC-targeted delivery of simvastatin was designed using nanotechnology. The anti-HCC effect and toxicity of the nano-drug was evaluated in both intra-hepatic and hemi-splenic inoculated mouse fibrotic HCC model. Results LSEC capillarization is associated with fibrotic HCC progression and poor survival in both murine HCC model and HCC patients. We further found simvastatin restores the quiescence of activated hepatic stellate cells (aHSCs) via stimulation of KLF2-NO signaling in LSECs, and up-regulates the expression of CXCL16 in LSECs. In intrahepatic inoculated fibrotic HCC mouse model, LSEC-targeted nano-delivery of simvastatin not only alleviates LSEC capillarization to regress the stromal microenvironment, but also recruits natural killer T (NKT) cells through CXCL16 to suppress tumor progression. Together with anti-programmed death-1-ligand-1 (anti-PD-L1) antibody, targeted-delivery of simvastatin achieves an improved therapeutic effect in hemi-splenic inoculated advanced-stage HCC model. Conclusions These findings reveal an immune-based therapeutic mechanism of simvastatin for remodeling immunosuppressive tumor microenvironment, therefore providing a novel strategy in treating HCC. Graphical Abstract